The rise of China and structural changes in Korea and Asia - Ito, Takatoshi 1950-.; Hahn, Chin Hee. (Cheltenham, UK Edward Elgar, 2010)
The rise of China and its integration with the rest of the world is probably one of the most important developments in today's global economy, but what impacts has China's rise had on the neighboring economies of East Asia? This book brings together research for those who wish to understand China's rise and policy challenges.
Keywords: China -- Economic policy -- 1976-2000.; China -- Economic policy -- 2000-.; China -- Economic conditions -- 1976-2000.; China -- Economic conditions -- 2000-.; East Asia -- Economic conditions; East Asia -- Economic policy